Clumped isotopes measured in planktonic foraminifera species T. trilobus and G. tumida from IODP Site U1488 (Meinicke et al., 2021) (IEDA: EarthChem Library)
This dataset contains D47, d18O and d13C data from Site U1488 in the central Western Pacific Warm Pool measured in two species of plantonic foraminifera, Trilobatus trilobus and Globorotalia tumida. The data covers several time intervals from the last 6 Myrs. In addition to the mean sample data used in the publication, replicate-level raw data is provided to allow for reprocessing of the data.